Notice of the Discovery of a Stone Cist and Urns at the Cuninghar, Tillicoultry;: With Notes on the Contents and the Sculptured Covering Stone of the cist; and on the Microscopical Examination of the Fibrous or Hairy Substance found in the Cist - Robertson, R; Black, George F; Struthers, John (Proceedings of the Society of Antiquaries of Scotland, 1895)